Der Geist macht lebendig : Die Lektüre von 1Joh im afrikanischen Kontext - Watt, Jan G. van der (Protokolle zur Bibel, 2000)
After general observations on symbolic narratives, the article provides overviews of important elements in the symbolic narratives of African traditional religion and of 1 John, respectively. Then it presents a reading of 1 John in Africa in light of these two symbolic narratives, with particular attention to the themes of group orientation, community, realized eschatology, being born into the family of God, the Spirit, the role of the prophet, the role of Christ, and access to the Father.–D.J.H. Abstract Number: NTA45-2001-1-448
free
Keywords: Epistles-Revelation – Catholic Epistles